Hepatitis C therapy with grazoprevir/elbasvir and glecaprevir/pibrentasvir in patients with advanced chronic kidney disease: data from the German Hepatitis C-Registry (DHC-R). Issue 1 (January 2022) - Stein, Kerstin; Stoehr, Albrecht; Klinker, Hartwig; Teuber, Gerlinde; Naumann, Uwe; John, Christine; Heyne, Renate; Serfert, Yvonne; Niederau, Claus; Zeuzem, Stefan; Berg, Thomas; Wiegand, Johannes
Abstract : Objectives: Grazoprevir/elbasvir and glecaprevir/pibrentasvir (G/P) are the two preferred treatment options for patients with chronic hepatitis C virus (HCV) infection and a glomerular filtration rate (GFR) <30 mL/min. Both therapies have been separately analyzed in different real-life cohorts; however, a direct comparison has not been performed so far. We, therefore, analyzed safety and effectiveness of both regimens in a concerted real-life population. Methods: The Germany Hepatitis C-Registry is a prospective national real-world registry. The analysis is based on 2773 patients with documented GFR at baseline treated with grazoprevir/elbasvir ( N = 1041), grazoprevir/elbasvir + ribavirin ( N = 53) and glecaprevir/pibrentasvir ( N = 1679). Results: A total of 93 patients with GFR <30 mL/min were treated with grazoprevir/elbasvir ( N = 56), grazoprevir/elbasvir + ribavirin ( N = 4), and glecaprevir/pibrentasvir ( N = 33). They suffered significantly more frequent from diabetes mellitus, hypertension, and coronary heart disease than individuals with GFR >30 mL/min and showed the following baseline characteristics: 20.4, 55.9, 3.2, 12.9, and 5.3% were infected with HCV-genotypes 1a, 1b, 2, 3, and 4; 12.9% suffered from liver cirrhosis; 80.1% were treatment-naïve. Baseline characteristics except distribution of HCV-genotype 1b ( n = 43/52 treated with grazoprevir/elbasvir) and sustained virologic response rates (SVR12) did not differ significantly between glecaprevir/pibrentasvir (SVR12: 100%) and grazoprevir/elbasvir (SVR12: 97.9%). Fatigue, headache, abdominal discomfort, and arthralgia were the most frequently reported adverse events without a statistical difference between grazoprevir/elbasvir and glecaprevir/pibrentasvir. Conclusion: In patients with chronic hepatitis C and a baseline GFR ⩽30 mL/min grazoprevir/elbasvir and glecaprevir/pibrentasvir show an equally favorable safety profile and antiviral efficacy and can both be recommended for real-life use.